Un edificio olvidado de la Sevilla americana: Las Reales Atarazanas - Pablo E. Pérez-Mallaína (Caravelle)
Among a great number of buildings and places which remind Sevilla’s relation with the American world, very seldom are the Reales Atarazanas taken into consideration. It’s an old medieval naval dockyard which has been partially conserved and which was the first seat of the Casa de Contratación. It was also used as a storehouse by many conquistadors and traders belonging to the Carrera de Indias and, at the end of the sixteenth century, occupying part of its surface, stood the Customs where custom dues concerning trade with America were paid. This article aims to rediscover the Atarazanas for historiography and to analyze its different uses as a way of seeing different stages of the development of Sevilla in relation to the New World.